Metastasis of Ciliary Body Melanoma to the Contralateral Eye: A Case Report and Review of Uveal Melanoma Literature - Nouritza M. Torossian; Roy T. Wallace; Wen-Jen Hwu; Agop Y. Bedikian (Case Reports in Oncological Medicine)
Many types of cancers metastasize to the eye. However, uveal melanoma metastasizing to the contralateral choroid is very rare. We report the case of a 68-year-old man with history of treated uveal melanoma of the right eye that developed metastasis to the liver and the choroid of the left eye. Ten years earlier, he was diagnosed to have uveal melanoma of the right eye and was initially treated with plaque radiotherapy. Two years later, upon progression of the disease in the right eye he had enucleation of the eye. We describe the patient’s clinical history, the diagnosis of recurrent disease in the contralateral eye, therapy of the left eye, and systemic metastasis. In addition, we reviewed the published medical literature and described the recent advances in the management of uveal melanoma.